South Korean election: return of the conservatives - King, Sean (2022)
South Korea’s presidential election this week is turning out to be a nail-biter. Incumbent Moon Jae-In is out of the race as the law only allows for one five-year term. The conservatives look set to come back, but whoever wins, there are foreign policy and regional security implications.